Threads to biodiversity and economic approaches to development of land use as its protection - Demydenko, L. (Land Management, Cadastre and Land Monitoring, 2017)
In the article the understanding of ecological and economic instruments for biodiversity conservation as a system of market, legal and regulatory, institutional arrangements and policies for sustainable development of land use.In terms of European integration, which is the basis of foreign policy identity Ukraine, acquires particular significance modernization of the state, forming an effective and efficient system of public administration (Public Administration), able to introduce systematic and consistent decisions, submission of all tasks of foreign and domestic policy achievement of the conditions and criteria membership in the European Union, particularly in the field of biodiversity conservation and land use management of protected areas, as its component.The signing of the Association Agreement between Ukraine, on one hand, and the European Union and its Member States, of the other part (the Agreement) offers new opportunities and creates new standards in various areas of public life, including environmental protection. Sectoral cooperation in the field of environmental protection in the Agreement stipulated in Chapter 6, which is called "Environment" Chapter V «economic and sectoral cooperation." For Ukraine, the implementation of EU legislation in the field of the environment occurs within the eight sectors governed by 29 sources of law (Directives and Regulations) of the EU in this area. Directive and Regulation establishes common rules and standards that need to be transposed (transferred) to domestic law. These rules and standards are not the subject of discussion and be completely achieved, otherwise stipulated penalties. Unlike modern environmental legislation of Ukraine, which in many respects is a declarative sources of EU law determine the quantitative and qualitative results, which should reach every country within a specified period of time. The feature of EU Directives is that States must adapt their legislation to achieve the goals set Directives, but decide for themselves how they achieve it.The main causes of biodiversity loss necessitated justification of various economic tools for conservation, both market and non-market, fiscal, legal, management, etc., depending on the natural features and economic systems and customs of a country. These measures provide a set of tools to overcome the negative features of the market, policy and institutional failures and to encourage people to preserve biodiversity in the course of business. Economic instruments can be used to improve the efficient allocation and use of natural and environmental resources so as to better reflect the social costs of using these resources. Eliminating the shortcomings of the national economic and environmental models of biodiversity management and environmental land use, finding ways of upgrading will become an effective instrument for the adaptation of the European model of sustainable use and conservation of all components of biological diversity.In these circumstances, especially important is the creation of reliable theoretical and methodological principles of adaptation experience of the European system of protected areas, implementing the use of ecological and economic tools and mechanisms to encourage local authorities and communities in which the impact of conditionality EU will promote reform of state environmental control in Ukraine according to European standards. Keywords: ecological and economic tools, biodiversity, insentives, protected areas. land use.